Effect of Febrile Neutropenia Guideline’s Implementation on Death Rate in Dharmais Cancer Center Hospital - Ranuhardy, Dody (UI Scholars Hub, 2018)
Febrile neutropenia may have a high morbidity and mortality impact for the patient. The death rate of febrile neutropenia in 2002 was 38.8%, while in 2009 was 27.3%. The difference in mortality rates could caused by several factors such as availability of the Neutropenic Fever Management Guidelines in 2006, in addition to infrastructure, human resources and equipment. This study aims to determine the effect of the availability of the guideline and other factors to cancer mortality rate in the compromised immune isolation room of Dharmais Hospital. This study is a cross-sectional retrospective study which investigate mortality rates and compare with adherence to febrile neutropenia guidelines for the period 2008-2012. Data were taken from the patient's medical record file, then analyzed using univariate and bivariate analysis. The mortality rate in the period 2008-2012 was 20,7%. The effect of age, sex, and degree of risk factor on mortality was not significantly different (p=0,409, p=0,404, and p=0,324). The proportion of deaths was higher in patients borne by third parties (26.8%) than in the case of personal (10%) although not statistically significant (p=0,065). Of the three types of adherence, only one had a significant effect of adherence to treatment flow (p=0,033).